2022
DOI: 10.2147/ijn.s384196
|View full text |Cite
|
Sign up to set email alerts
|

Short-Wavelength Aggregation-Induced Emission Photosensitizers for Solid Tumor Therapy: Enhanced with White-Light Fiber Optic

Abstract: Background White-light photodynamic therapy (wPDT) has been used in the treatment of cancer due to its convenience, effectiveness and less painful. However, the limited penetration of white-light into the tissues leads to a reduced effectiveness of solid tumor treatment. Methods Two short-wavelength aggregation-induced emission (AIE) nanoparticles were prepared, PyTPA@PEG and TB@PEG, which have excitation wavelengths of 440 nm and 524 nm, respectively. They were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…PI staining is commonly used to indicate late apoptosis or cell death; while, CMFDA staining is used to indicate survival or live cells. [22] As expected, the co-staining results showed that the tumor cells were killed when both M@PFC and light conditions were present together, as shown in Figure 2D. This indicates that M@PFC has the capacity to induce cell death in 4T1 cells under light conditions.…”
Section: Photodynamic Therapy and Immunological Effects Of M@pfc In V...supporting
confidence: 77%
“…PI staining is commonly used to indicate late apoptosis or cell death; while, CMFDA staining is used to indicate survival or live cells. [22] As expected, the co-staining results showed that the tumor cells were killed when both M@PFC and light conditions were present together, as shown in Figure 2D. This indicates that M@PFC has the capacity to induce cell death in 4T1 cells under light conditions.…”
Section: Photodynamic Therapy and Immunological Effects Of M@pfc In V...supporting
confidence: 77%
“…16(a), white light photodynamic therapy (wPDT) has been used in the treatment of cancer because of its convenience, effectiveness, and low pain. Two short-wavelength aggregationinduced luminescence (AIE) nanoparticles (PyTPA@PEG and TB@PEG) were prepared for the further killing of cancer cells by reactive oxygen species [144]. The fiber-mediated PDT enhances tissue penetration, which significantly induces tumor elimination and maximizes the therapeutic effect by irradiating inside the tumor.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…Photodynamic therapy mainly depends on light-harvesting photosensitizers to ingest light of specific wavelengths and then produce reactive oxygen species (ROS), consequently causing oxidative harm to cancer cells ( Zhang et al, 2022b ). However, most photosensitizers need to be activated by short-wavelength light from the ultraviolet (UV) to visible light regions and have low tissue penetration, leading to unacceptable and inadequate therapeutic impacts.However, photodynamic therapy based on X-ray and near-infrared light requires long-term exposure to outside light, which might lead to unanticipated tissue damage because of radiation damage and thermal effects, respectively ( Meng et al, 2022c ). Recently, Shu et al (2021) successfully developed a rechargeable photodynamic immune hydrogel capable of persistent luminescence by introducing a persistent luminescent material and an immune adjuvant (R837) into alginate-like substances.…”
Section: Hydrogels Can Be Used In Multiple Treatments For Cancermentioning
confidence: 99%